2017
DOI: 10.1210/jc.2016-3287
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatic Protection Effects of Hepassocin in Hyperglycemic Crisis

Abstract: Increased hepassocin secretion in hyperglycemic crisis might offset the deleterious effects of hyperglycemia on hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…The formation of triacylglycerol‐enriched lipid droplets and induction of autophagy by OLA are protective mechanisms against SFA‐induced lipotoxicity (Mei et al, ). In this study, we provided evidence that OLA‐induced HPS expression might play an important role in the protective effects of unsaturated fatty acids, in consistent with previous study (Ou et al, ). It was known that HPS regulates cell proliferation and protects hepatic cells from chemical‐induced liver injury (Li et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The formation of triacylglycerol‐enriched lipid droplets and induction of autophagy by OLA are protective mechanisms against SFA‐induced lipotoxicity (Mei et al, ). In this study, we provided evidence that OLA‐induced HPS expression might play an important role in the protective effects of unsaturated fatty acids, in consistent with previous study (Ou et al, ). It was known that HPS regulates cell proliferation and protects hepatic cells from chemical‐induced liver injury (Li et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…FGL1 promotes the proliferation of hepatocytes via an extracellular signal‐regulated kinase 1/2 (ERK1/2)‐dependent autocrine mechanism and exhibited protective effects during liver injury . In addition, FGL1 has a rescue role in hyperglycemic crises . Moreover, we showed that FGL1 has an important role in the development of NAFLD and insulin resistance (IR) .…”
Section: Introductionmentioning
confidence: 93%
“…16 In addition, FGL1 has a rescue role in hyperglycemic crises. 17 Moreover, we showed that FGL1 has an important role in the development of NAFLD and insulin resistance (IR). 18,19 Overexpression of FGL1 in the liver increased hepatic lipid accumulation and IR in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal physiological conditions, FGL1 is secreted mainly by hepatocytes in the liver (some of which may also exist in the pancreas) [50]. It is now clear that FGL1 is the product of hepatocyte regeneration and participates in hepatocyte mitosis and liver energy utilization (including lipid metabolism and blood glucose regulation) [54,68,69]. Apart from the above functions, FGL1 can also be detected in the plasma as an acute reactant [70], implying that FGL1 secreted by the liver acts not only on hepatocytes (autocrine) but also on other tissues, such as muscle and brown adipose tissues (telecrine) (Fig.…”
Section: Structure and Distribution Of Fgl1mentioning
confidence: 99%
“…Under stimulation by metabolic factors (hyperglycemia, hyperlipidemia, hormones, etc. ), the liver secretes FGL1 and participates in the blood circulation [52,69,71]. This function of FGL1 acts on brown adipose tissue [54,56], regulates body productivity and maintains body temperature.…”
Section: Structure and Distribution Of Fgl1mentioning
confidence: 99%